2008
DOI: 10.1088/1126-6708/2008/05/018
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the Poisson sigma model

Abstract: We show how to carry out the gauging of the Poisson sigma model in an AKSZ inspired formulation by coupling it to a generalization of the Weil model worked out in ref. [31]. We call the resulting gauged field theory, Poisson-Weil sigma model. We study the BV cohomology of the model and show its relation to Hamiltonian basic and equivariant Poisson cohomology. As an application, we carry out the gauge fixing of the pure Weil model and of the Poisson-Weil model. In the first case, we obtain the 2-dimensional ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 50 publications
(109 reference statements)
1
23
0
Order By: Relevance
“…The model that we are going to discuss was considered in [15,4,11]. The graded geometric formulation of the equivariant formulation and its AKSZ theory that we are going to use was discussed in [4].…”
Section: Definition Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The model that we are going to discuss was considered in [15,4,11]. The graded geometric formulation of the equivariant formulation and its AKSZ theory that we are going to use was discussed in [4].…”
Section: Definition Of the Modelmentioning
confidence: 99%
“…We consider here a different gauge fixing of the Lie algebra sector that recovers the so called topological Yang-Mills theory in two dimensions, considered by Witten in [14]. This connection was already established in [15]; here we use a slightly different gauge fixing and emphasize the relation between the residual gauge symmetry and the gauge multiplet of supersymmetry. The basic tool for introducing topological Yang-Mills theory is the gauge multiplet of 2d supersymmetry.…”
Section: The Gauge Multiplet and Topological Yang-millsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BFV-AKSZ model corresponding to (5.23) is the sigma model proposed by Zucchini in [35,36] as Poisson-Weil sigma models and by Signori in [33] under the name of JPSM. In [36] it is shown that a sector of the underlying BV-cohomology is related to the equivariant Poisson cohomology of (M, π M ). In Appendix D we clarify this relation, by relating the cohomology of the target QP-manifold to Poisson equivariant cohomology.…”
Section: Remark 23mentioning
confidence: 99%
“…In a series of recent papers [35,36] the procedure of gauging and reduction for the Poisson Sigma model (PSM in short) has been considered. The model is constructed when there is an action of a Lie group G on a Poisson manifold M by Poisson diffeomorphisms and this action is hamiltonian with momemntum map µ : M → g * .…”
Section: Introductionmentioning
confidence: 99%